Effectiveness of a WeChat Combined Continuous Flash Glucose Monitoring System on Glycemic Control in Juvenile Type 1 Diabetes Mellitus Management: Randomized Controlled Trial - Xu Y (Dove Medical Press, 2021)
Yuejie Xu,1,* Lei Xu,1,* Weijing Zhao,1 Qing Li,1 Ming Li,1 Wei Lu,1 Hui Zeng,1 Jinhua Yan,2 Daizhi Yang,2 Wei Wu,3 Jianping Weng,2 Jiemin Pan,1 Fang Liu1 1Department of Endocrinology and Metabolism, Shanghai Jiao Tong University Affiliated Sixth People’s Hospital, Shanghai Clinical Center for Diabetes, Shanghai Key Clinical Center for Metabolic Disease, Shanghai Diabetes Institute, Shanghai Key Laboratory of Diabetes Mellitus, Shanghai, 200233, People’s Republic of China; 2Department of Endocrinology and Metabolic Disease, The Third Affiliated Hospital of Sun Yat-Sen University, Guangzhou, 510630, People’s Republic of China; 3Department of Pediatrics, Tongji Hospital, Wuhan Tongji Medical University, Wuhan, Hubei, 430030, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jiemin Pan; Fang LiuDepartment of Endocrinology and Metabolism, Shanghai Jiao Tong University Affiliated Sixth People’s Hospital, Shanghai Clinical Center for Diabetes, Shanghai Key Clinical Center for Metabolic Disease, Shanghai Diabetes Institute, Shanghai Key Laboratory of Diabetes Mellitus, 600 Yishan Road, Xuhui District, Shanghai, 200233, People’s Republic of ChinaTel +86-18930173803Email lilypjm@hotmail.com; f-liu@sjtu.edu.cnPurpose: Smartphones have received increasing attention and achieved positive outcomes in diabetes intervention. The widespread use of WeChat in China provides an opportunity for self-management practices in patients with diabetes. Nevertheless, how to combine the strengths of the WeChat platform with traditional medical strategy remains to be explored. This study aimed to evaluate the efficacy of a novel flash glucose monitoring device combined with the WeChat platform in juvenile type 1 diabetes management.Patients and Methods: A total of 60 juvenile patients with type 1 diabetes were randomly assigned into three groups: a blood glucose self-monitoring group (group A), a flash glucose monitoring (group B), and a flash glucose monitoring combined WeChat-interactive management group (group C). The intergroup differences in demographics, biochemical indicators, and questionnaire scores of the Diabetes Monitoring and Treatment Satisfaction Questionnaire and Diabetes Specific Quality of Life assessment were compared at the baseline and after 6 months.Results: After the 6-month intervention, groups B and C showed significantly lower glycated hemoglobin A1c (HbA1c) levels compared to those observed at baseline (both P < 0.05), with the largest decrease observed in group C (group B vs group C, P =0.04). Hypoglycemic episodes per month decreased from baseline in groups B and C (both P < 0.05) and were more significant in group C (P < 0.001). In addition, the DMTSQ scores increased in the 6th month in all groups (all P < 0.05), and the largest rise in scores was found in group C, followed by groups B and A. The DQOL scores in groups B and C decreased significantly from the baseline (both P < 0.05), with no change in group A.Conclusion: Flash glucose monitoring combined with the WeChat-interactive system may help achieve sustained glycemic control and higher satisfaction in patients with juvenile type 1 diabetes.Trial Registration: This study was registered at chictr.org.cn, number ChiCTR1900025495. Registered 29 August 2019.Keywords: WeChat, type 1 diabetes, self-management, glycated hemoglobin A1c